A Literatur Review of Common Outcome in Cognitive Remediation for Schizophrenia - Sadarwati Sadarwati; Warih Andan Puspitosari (IJNP (Indonesian Journal of Nursing Practices), 2021)
Background: People with schizophrenia experience a change especially in the cognitive aspect, and therefore require immediate intervention to improve their cognitive and other aspects. Cognitive remediation is a program that has been developed with promising results. Objective: to review the literature on outcomes in general from the provision of cognitive remediation in people with schizophrenia.Method: Searching relevant literature on relevant databases, i.e., Pubmed, Ebsco, Cochrane, JSTOR, and the Google Scholar search engine, using keywords: cognitive remediation, schizophrenia, therapy.Result: Taken from reviewing 21 relevant articles. Cognitive remediation affects cognitive function, functional ability and problem-solving, social skill and cognition, clinical symptoms, neural outcome, quality of life, self-esteem, and cost-utility analysis.Conclusions: Common outcomes in CRT (Cognitive Remediation Therapy) administration in people with schizophrenia have been identified. Improvement of cognitive function was defined to be the most commonly measured outcome in the study.